- 1-800-665-6601
- info[email protected]

Here each square root radical should be simplified further.

√3 cannot be simplified further as it is already in its simplified form since no number is repeating twice inside the radical to be pulled out.

And we have

So, √3 + √75 = 1√3 + 5√3 = (1 + 5) √3 = 6√3.

(They are like terms since they have the same radical √3 and hence can be added).

Hence the value of the expression, √3 + √75 is = 6√3.

Here each square root radical should be simplified further.

√3 cannot be simplified further as it is already in its simplified form since no number is repeating twice inside the radical to be pulled out.

And we have

So, √3 * √75 = √3 * 5√3 = 5 * √(3 * 3) = 5 * 3= 15.

Hence the value of the expression, √3 *√75 is = 15.